The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s12034-015-1019-4
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotube-based coatings on titanium

Abstract: This paper reports results of the modification of titanium surface with multiwalled carbon nanotubes (CNTs). The Ti samples were covered with CNTs via electrophoretic deposition (EPD) process. Prior to EPD process, CNTs were functionalized by chemical treatment. Mechanical, electrochemical and biological properties of CNT-covered Ti samples were studied and compared to those obtained for unmodified titanium surface. Atomic force microscopy was used to investigate the surface topography. To determine micromecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Several results confirm the hypothesis that the carbon component may act as chondrogenic material [51,52]. Carbon materials, including carbon fibres and carbon nanotubes, have been successfully used in the treatment of cartilage defects.…”
Section: Resultssupporting
confidence: 70%
“…Several results confirm the hypothesis that the carbon component may act as chondrogenic material [51,52]. Carbon materials, including carbon fibres and carbon nanotubes, have been successfully used in the treatment of cartilage defects.…”
Section: Resultssupporting
confidence: 70%
“…Thanks to this, they are increasingly applied in medicine and diagnostics, including tissue engineering [1,2]. These two-dimensional carbon structures are used, among others, to functionalize materials designed for implants, where CNTs can support osseointegration [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The biocompatibility of CNTs in orthopedic applications was established by in vitro studies, which showed accelerated bone growth and increased proliferation and differentiation of osteoblasts [5][6][7][8][9][10]. The most popular kind of metal substrate for CNTs is titanium [3,[11][12][13][14][15][16][17][18], which combines some beneficial mechanical properties and biocompatibility with a chemical in vivo susceptibility [11]. Several studies evaluated the body's reaction in the presence of carbon nanotubes, demonstrating a high vitality of osteoblasts compared to the pure titanium substrate [14][15][16]19].…”
Section: Introductionmentioning
confidence: 99%
“…Carbon micro-and nanofibrous materials obtained by heat treatment of the polymer precursor (carbonization) at low temperatures (about 1000°C) integrate well with tissues and can undergo a slow oxidation in the biological environment, turning into organic forms that do not pose a threat to the body [23,24]. Our research shows that both the micro and carbon nanofibers have a potential in the treatment and regeneration of the cartilage [25,26].…”
Section: Introductionmentioning
confidence: 74%
“…One of the objectives of the surface modification of carbon nanofibers is to develop an active material that could be used to regenerate osteochondral tissue, e.g., for laryngology. The previous literature reports indicate that carbon materials, including carbon fibers and carbon nanotubes, may act as substrates with chondrogenic properties [25,26]. Thus, the modified carbon nanofibers with a Si/Ca sol may be suitable substrates for osteochondral tissue.…”
Section: Resultsmentioning
confidence: 99%